Evaluation of cement-retained versus screw-retained implant-supported restorations for marginal bone loss: A systematic review and meta-analysis - Araujo Lemos, Cleidiel Aparecido [UNESP]; Souza Batista, Victor Eduardo de [UNESP]; Faria Almeida, Daniel Augusto de [UNESP]; Santiago Junior, Joel Ferreira; Verri, Fellippo Ramos [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier B.V., 2016)
Statement of problem. No consensus has been reached on which retention system, cement- or screw-retained, is best to avoid bone loss around the implant of a fixed implant-supported restoration. Purpose. The purpose of this systematic review and meta-analysis was to compare cement- and screw-retained retention systems in fixed implant-supported restorations in terms of marginal bone loss, implant survival, and prosthetic complications. Material and methods. A comprehensive search of studies published from January 1995 to March 2015 and listed in the PubMed/MEDLINE, Embase, Scopus and the Cochrane Library databases was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) statement. The meta-analysis was based on the Mantel-Haenszel and inverse variance methods. Marginal bone loss was the continuous outcome measure evaluated by mean difference (MD), and implant survival and prosthetic complications were the dichotomous outcome measures evaluated by risk ratio (RR), both with corresponding 95% confidence intervals (CI). Results. The 20 studies selected for review evaluated 2139 participants, whose mean age was 47.14 years and who had received 8989 dental implants. The mean follow-up was 65.4 months (range: 12-180 months). Results of the MD for marginal bone loss showed statistically significant differences in favor of the cement retained prosthesis (P=.04; MD: -0.19; CI: -037 to -0.01). The implant survival rate was higher for the cement-retained prosthesis (P=.01; RR: 0.49; CI: 028 to 0.85), and the prosthetic complication rate was higher for the screw-retained prosthesis (P=.04; RR: 052; CI: 0.28 to 0.98). Additional analysis of the mean plaque index did not show differences between retention systems (P=.58; MD: 0.13; CI: 0.32 to 0.57). Conclusions. The current meta-analysis indicated that cement-retained, fixed implant-supported restorations showed less marginal bone loss than screw-retained, fixed implant-supported restorations during the follow-up period, which ranged from 12 to 180 months. However, the small difference between the mean values may not show clinical significance. The rates of prosthetic complication and implant survival also compared favorably with cement-retained prostheses.